BP-MAC: A High Reliable Backoff Preamble MAC Protocol for Wireless Sensor Networks - Alexander Klein; Jirka Klaue; Josef Schalk (Electronic Journal of Structural Engineering, 2009)
Many Media Access Control (MAC) protocols for Wireless Sensor Networks (WSN) use varia-tions of the popular Carrier Sense Multiple Access (CSMA) protocol due to its simplicity and its high perfor-mance in low traffic scenarios. However, CSMA does not always  represent a good choice for WSNs since typical low power transceivers require a significant time to switch between receiving and transmitting and vice versa. Sensor nodes are not able to detect a busy channel during the switching. Thus, the collision proba-bility in WSNs is very high in case of correlated event-driven traffic. In this paper we introduce the BP-MAC protocol that uses a backoff preamble with variable length in order to mitigate the effect of Clear Channel As-sessment (CCA) delay.